A scoping review: Nurses' workload in patients for fall risk screening - A., Oktarisa Khairiyah; Shaluhiyah, Zahroh; Purnami, Cahya Tri (Interdisciplinary Social Studies, 2023)
Half of all falls result in injury, of which 10% are seriously impacted. Direct medical expenses resulting from falls amount to nearly $30 billion annually. Nurses must engage cognitive, affective, and actions that put patient safety first. The breadth of the nurse's role can allow for the risk of errors in service. This scoping review is prepared to discuss the effect of nurse workload in screening the risk of falls on patients. The method used here is scoping review which is used to develop a 'map' regarding the effect of nurse workload in screening the current patient's fall risk. The search databases used in this writing include: SINTA, PubMed, EBSCOhost, and SagePub. The search was conducted on October 16, 2023 and the included studies were research taken in 2013-2023. The authors found seven scientific journals that discuss the effect of workload in screening patient fall risk. The four journals came from Indonesia, one journal each from Brazil, Taiwan, and Canada. Workload is consistently associated with suboptimal fall risk screening. This is because nurses will be busy doing other things, so screening and monitoring patients from the risk of falling cannot be done properly.